Energetics and evolution: an emerging research domain - Leonard, W; Ulijaszek, S (Wiley, 2002)
The study of energetics is important to human biology because the availability and utilization of food energy influence health, survival, and reproduction. Over the last decade, human biologists, biological anthropologists, and other evolutionary scientists have increasingly come to recognize the importance of energy dynamics in shaping evolutionary processes. Thus far, different lines of energetics research have been conducted largely in isolation from one another. This thematic collection examines topics of evolutionary energetics from several different perspectives, drawing together research from human paleontology, comparative primate and mammalian biology, human population biology, and mathematical modeling. It represents a starting point for further integrative research on human evolutionary energetics.